Medication administration in Australian residential aged care: A time‐and‐motion study. Issue 1 (14th April 2020) - Chen, Esa Y. H.; Bell, J. Simon; Ilomäki, Jenni; Corlis, Megan; Hogan, Michelle E.; Caporale, Tessa; Van Emden, Jan; Westbrook, Johanna I.; Hilmer, Sarah N.; Sluggett, Janet K.
Abstract: Rationale/aim: Medication administration is a complex and time‐consuming task in residential aged care facilities (RACFs). Understanding the time associated with each administration step may help identify opportunities to optimize medication management in RACFs. This study aimed to investigate the time taken to administer medications to residents, including those with complex care needs such as cognitive impairment and swallowing difficulties. Method: A time‐and‐motion study was conducted in three South Australian RACFs. A representative sample of 57 scheduled medication administration rounds in 14 units were observed by a single investigator. The rounds were sampled to include different times of day, memory support units for residents living with dementia and standard units, and medication administration by registered and enrolled nurses. Medications were administered from pre‐prepared medication strip packaging. The validated Work Observation Method By Activity Timing (WOMBAT) software was used to record observations. Results: Thirty nurses were observed. The average time spent on scheduled medication administration rounds was 5.2 h/unit of average 22 residents/day. The breakfast medication round had the longest duration (1.92 h/unit). Resident preparation, medication preparation and provision, documentation, transit, communication, and cleaning took an average of 5 minutes per resident per round. Medication preparation and provision comprised 60% of overall medication round time and took significantly longer in memory support than in standard units (66 vs 49 seconds per resident per round for preparation, 79 vs 58 for provision; P < .001 for both). Almost half (42%) of tablets/capsules were crushed in memory support units. The time taken for medication administration was not significantly different among registered and enrolled nurses. Conclusions: Nurses took an average of 5 minutes to administer medications per resident per medication round. Medication administration in memory support units took an additional minute per resident per round, with almost half of tablets and capsules needing to be crushed.